Intestinal permeability and peripheral immune cell composition are altered by pregnancy and adiposity at mid- and late-gestation in the mouse - Ribeiro, Tatiane A; Breznik, Jessica A; Kennedy, Katherine M; Yeo, Erica; Kennelly, Brianna K E; Jazwiec, Patrycja A; Patterson, Violet S; Bellissimo, Christian J; Anhe, Fernando F; Schertzer, Jonathan D; Bowdish, Dawn M E; Sloboda, Deborah M (bioRxiv, 2022)
It is clear that the gastrointestinal tract influences metabolism and immune function. Most studies to date have used male test subjects, with a focus on effects of obesity and dietary challenges. Despite significant physiological adaptations that occur across gestation, relatively few studies have examined pregnancy-related gut function. In this study, we investigated the impacts of pregnancy and maternal adiposity on the structure of the maternal intestinal epithelium and in vivo intestinal permeability, as well as peripheral blood immunophenotype, using cohorts of control (CTL) and high fat (HF) fed non-pregnant female mice and pregnant mice at mid- (embryonic day (E)14.5) and late (E18.5) gestation. We found that small intestine length increased between non-pregnant mice and dams at late-gestation, but ileum villus length, and ileum and colon crypt depths and goblet cell numbers remained similar. Compared to CTL-fed mice, HF diet reduced small intestine length, as well as ileum crypt depth and villus length, in both non-pregnant and pregnant mice. Goblet cell numbers were only consistently reduced in HF-fed non-pregnant mice. Pregnancy increased in vivo gut permeability, with a greater effect at mid- versus late-gestation. Non-pregnant HF-fed mice had greater gut permeability, and permeability was also increased in HF-fed pregnant dams at mid- but not late-gestation. The loss of maternal gut barrier in HF-fed dams at mid-gestation coincided with changes in maternal blood and bone marrow immune cell composition, including an expansion of circulating inflammatory Ly6Chigh monocytes. In summary, pregnancy has temporal effects on maternal intestinal structure and barrier function, and on peripheral immunophenotype, which are further modified by HF diet-induced maternal adiposity. These data highlight the importance of considering pregnancy as a factor in intestinal modifications and the potential for pregnancy and diet to interact on modifying maternal gut function. Impairments in maternal intestinal and immune adaptations to pregnancy will have long term consequences in the offspring. Competing Interest Statement The authors have declared no competing interest.